Apley and Solomon's system of orthopaedics and trauma - Blom, Ashley; Warwick, David; Whitehouse, Michael; Solomon, Louis (CRC Press, 2018)
Now in its Tenth Edition and in continuous publication since 1959, Apley & Solomon's System of Orthopaedics and Trauma is one of the world's leading textbooks of orthopaedic surgery. Relied upon by generations of orthopaedic trainees the book remains true to the teaching principles of the late Alan Apley and his successor Professor Louis Solomon. This new edition is fully revised and updated under the leadership of new editors. It retains the familiar 'Apley' philosophy and structure, and is divided into three major sections: General Orthopaedics, Regional Orthopaedics and Trauma, thus enabling readers to gain the knowledge they need for their lifetime learning.